2010
DOI: 10.1038/nature09599
|View full text |Cite
|
Sign up to set email alerts
|

S-glutathionylation uncouples eNOS and regulates its cellular and vascular function

Abstract: Endothelial nitric oxide synthase (eNOS) is critical in the regulation of vascular function, and can generate both nitric oxide (NO) and superoxide (O2•−), which are key mediators of cellular signalling. In the presence of Ca2+/calmodulin, eNOS produces NO, endothelial-derived relaxing factor, from L-arginine (L-Arg) by means of electron transfer from NADPH through a flavin containing reductase domain to oxygen bound at the haem of an oxygenase domain, which also contains binding sites for tetrahydrobiopterin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
521
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 528 publications
(546 citation statements)
references
References 42 publications
19
521
1
5
Order By: Relevance
“…Glutathionylation, which involves formation of a reversible disulphide bond between glutathione and reactive cysteines on proteins with significant structural and functional consequences, is increasingly recognized in physiological and pathophysiological cell signaling 13. Of direct relevance to our objective, glutathionylation also mediates eNOS uncoupling in endothelial cells under oxidative stress 14. In contrast to uncoupling by depletion of the cofactor tetrahydrobiopterin (BH 4 ), which leads to O 2 •− generation in the oxidase domain of the enzyme instead of NO synthesis, uncoupling by glutathionylation of 2 highly conserved cysteine residues of eNOS leads to O 2 •− generation in the reductase domain and abolishment of NO production 14.…”
Section: Introductionmentioning
confidence: 99%
“…Glutathionylation, which involves formation of a reversible disulphide bond between glutathione and reactive cysteines on proteins with significant structural and functional consequences, is increasingly recognized in physiological and pathophysiological cell signaling 13. Of direct relevance to our objective, glutathionylation also mediates eNOS uncoupling in endothelial cells under oxidative stress 14. In contrast to uncoupling by depletion of the cofactor tetrahydrobiopterin (BH 4 ), which leads to O 2 •− generation in the oxidase domain of the enzyme instead of NO synthesis, uncoupling by glutathionylation of 2 highly conserved cysteine residues of eNOS leads to O 2 •− generation in the reductase domain and abolishment of NO production 14.…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in decreased synthesis of NO and potentiated superoxide production [127]. Additional regulation of endothelial NOS activity by disulfides was found when mass spectrometry analysis of aortas, which indicated that S-glutathiolation of Cys-689 and Cys-908 uncoupled endothelial NOS so that it generated superoxide instead of NO [106]. Thus NOS, like so many other enzymes reported to be Snitrosated, are also observed to form disulfides.…”
Section: Endothelial Nosmentioning
confidence: 95%
“…Increasing lines of evidence point to the important role of S-glutathionylation in the regulation of signaling and metabolic pathways in intact cellular systems. Indeed, Chen et al found that GSSG induced dose-dependent S-glutathionylation of human eNOS that was reversed by reducing agents β-mercaptoethanol or dithiothreitol [8] . S-glutathionylation of eNOS reversibly decreases NOS activity with a concomitant increase in ·O 2-generation primarily from the reductase domain.…”
Section: Research Highlightmentioning
confidence: 99%
“…Recently, Chen et al reported that S-glutathionylation of eNOS may be a unique mechanism for the redox regulation of eNOS [8] . It has been demonstrated previously that cysteine residues are critical for the maintenance of normal eNOS function [9] .…”
Section: Research Highlightmentioning
confidence: 99%